Implementasi Nilai-Nilai Etika Profesi Guru dalam Pembentukan Karakter Peserta Didik (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Character education is an important factor in preparing professional teachers, who not only have academic abilities but also good moral values. The importance of applying ethics in the profession greatly influences the development of students' character, because professional ethics provides guidelines for teachers in carrying out their duties. This research aims to analyze the ethical values ​​possessed by teachers and how they influence the development of students' character. The method used in this research is qualitative, which is carried out by reviewing the literature through books, journal articles and related documents. The research results show that the application of teacher professional ethics is manifested in: (1) integration of ethical values ​​during the learning process, (2) exemplary teachers as moral examples, and (3) cooperation between professional ethics and the culture of educational institutions. These three aspects make an important contribution in shaping student character, such as honesty, responsibility, discipline, empathy and integrity. This research also confirms that the quality of student character is greatly influenced by the teacher's ability to internalize and continuously apply professional ethical values.